Endocrine Therapy for Hormone Receptor-Positive Advanced Breast Cancer: A Nation-Wide Multicenter Epidemiological Study in China - Wu, Yun; Han, Yiqun; Yu, Pei; Ouyang, Quchang; Yan, Min; Wang, Xiaojia; Hu, Xichun; Jiang, Zefei; Huang, Tao; Tong, Zhongsheng; Wang, Shusen; Yin, Yongmei; et al. (Frontiers in Oncology, 2021)
Background: Clinical guidelines generally recommend endocrine therapy (ET) as first-line treatment of hormone receptor-positive advanced breast cancer (HR+ABC) whereas chemotherapy (CT) should be considered in the presence of life-threatening disease or limited clinical benefit after three sequential ET regimens. However, it is unclear if real-world clinical practice is in accordance with the current guidelines. This study was to present the real-world treatment patterns and ET regimens among HR+ABC patients in China. Methods: Using data from the Nation-wide Multicenter Retrospective Clinical Epidemiology Study of Female Advanced Breast Cancer in China (ClinicalTrials.gov identifier: NCT03047889), we investigated the clinicopathological characteristics, clinical profiles, and treatment patterns of HR+ABC patients from January 2012 to December 2014. Results: A total of 2342 patients with HR+ABC were included in this study. Our findings revealed that, in comparisons with those receiving initial CT (n = 1445), patients initiated ET (n =402) were significantly older, later recurrent after adjuvant treatment, with a lower rate of visceral involvement and a decreasing quantity of metastatic sites. A total of 1308 patients received palliative ET while only 18.9% patients (n=247) reached three lines of ET. Among patients completing more than one line of ET, the median treatment duration was 8 months for the first line, 6 months for the second line, and 3 months for the third line for patients receiving ET. In the advanced setting, the choices of palliative ET regimens were diverse, yet aromatase inhibitors (AIs) monotherapy was still as the overall mainstay of ET; in contrast, patients were less accessible to everolimus plus AIs regimen in this population. Conclusions: Less than one quarter of patients initiated palliative ET for HR+ABC in routine clinical practice. Patients who received multi-lines of ET experienced successive shorter durations following each lines of therapy. This real-life data provides a solid overview of ET for HR+ ABC from China, indicating unmet need for treatment options that improve the effectiveness of endocrine therapy.